ANALISIS PERUBAHAN FONEM PADA KATA SERAPAN BAHASA BELANDA KE BAHASA INDONESIA - Ramadhani, Jasmine Malaika; Nurafiani, Viona; Karunia, Dona Aji (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
In its development, Indonesian is inseparable from the influence of foreign languages. There are many words in the Indonesian language that come from other languages, which are then used by the community for daily language activities in Indonesian. The word is also called the term absorption word. This research aims to analyze phoneme changes through the writing of vowel and consonant phonemes and describe foreign language absorption words into Indonesian, this research focuses on Dutch as a foreign language that is absorbed into Indonesian. This research was conducted using descriptive qualitative method and also comparative linguistic approach. Therefore, this research will describe Dutch and Indonesian in detail. The data in this research is in the form of Dutch and Indonesian vocabulary. The data sources are Dutch dictionary and Indonesian dictionary. The data in this study were obtained using documentation, listening, and note-taking techniques. The results of this study show that there are changes in phonemes, namely changes in vowel phonemes and consonant phonemes which are characterized by changes in letters and pronunciation and there is also absorption of Dutch in Indonesian.